TINDAK TUTUR REPRESENTATIF HOTMAN PARIS HUTAPEA DALAM ACARA HOTMAN PARIS SHOW DI INEWS - Diva R Silalahi; Hasnah Faizah; Mangatur Sinaga (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study describes Hotman Paris Hutapea’s representative acting speech in the Hotman Paris show at the iNews. This study aims to describe the type and function of speech act representative Hotman Paris Hutapea. Research is a type of descriptive-qualitative. The data in the from representative speech of Hotman Paris Hutapea sourced from the video Hotman Paris Show in iNews. The instruments in the study were Hotman Paris Show videos transcribed and typed to get the correct research data. Technique of data collecting is done by documentation and technique of data collecting is done by documentation and technique of free involved ably. Data is taken from five videos begining December 2017 to January 2018, there are of representative speech acts: assertive, predictive, retrodictive, descriptive, ascriptive, informative, confirmative, conscientious, retractive, asentif, dissentive, dispitative, responsive, suggestive. Speech acts wich states, shows, reports, assesses, categorizes, references, informs, concludes, allows, recognizes, references, refutes, accepts, disagrees, objections, questions, responds, suggests, guesses, assumes.Key words: Speech, Representative, Hotman Paris Hutapea.